2021
DOI: 10.1109/access.2021.3066133
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Pooling and Collaborative Cache Management for NDN/IoT Networks

Abstract: Named Data Networking (NDN) has been recognized as a lever to the Internet of Things (IoT). One of the most founding features of NDN is in-network caching to improve data availability and reduce retrieval delays and network load. Despite the existence of several caching decision algorithms, the fetching and distribution of contents with minimum resource utilization remains a great challenge. In this paper, we propose an efficient caching technique named PoolCache that augments the effective caching capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Results showed that the proposed scheme decreased the caching cost while improving the overall network performance. The authors of [29] introduced PoolCache, where they forced caching at the edge of the network and disallowed caching at internal nodes of the network. PoolCache presents a good level of diversity and zero redundancy within each pool of routers.…”
Section: Ndn Caching Policiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Results showed that the proposed scheme decreased the caching cost while improving the overall network performance. The authors of [29] introduced PoolCache, where they forced caching at the edge of the network and disallowed caching at internal nodes of the network. PoolCache presents a good level of diversity and zero redundancy within each pool of routers.…”
Section: Ndn Caching Policiesmentioning
confidence: 99%
“…In this section, we first evaluate the performance of our proposed caching technique, PF-ClusterCache, and then we perform a comparative analysis with three different caching approaches. These are the well-known Leave Copy Everywhere LCE [27], which is used as a yardstick for comparison in many studies on caching in NDN; the Caching Fresh and Popular Content (CFPC) [23], which is, similar to PF-ClusterCache, an approach based on both popularity and freshness; and the PoolCache [29], which is, similar to PF-ClusterCache, a collaborative caching scheme based on pooling the cache storage of several nodes but with no explicit treatment of data popularity and no consideration of data freshness. The performance evaluation and the comparative analysis are conducted by simulation using the ndnSIM simulator [40,41].…”
Section: Performance Evaluation and Comparative Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The CCJRF-ICN protocol aims to perform superior to the ProbCache approach as it is efficient compared to the whole course caching method. For NDN based IoT networks, the authors in [27] have introduced an efficient collaborative caching mechanism called PoolCache that increases the caching capability of some defined clusters of a node. It requires very limited resources though attains better network performance.…”
Section: Related Workmentioning
confidence: 99%